Rural Educational Policies and Leadership in Neoliberalism: Comparative study between Jalisco, Coquimbo and Victoria. - Díaz Delgado, Miguel Ángel (2025)
This paper is the result of the initial phase of an international comparative study on educational policies for rural contexts and School Leadership, the analysis observed the Neoliberal Educational Policies from the Jalisco (Mexico), Victoria (Australia) States and the region of Coquimbo (Chile), providing historical references of the educational systems, the effects of these Policies on rural education and the School Leadership. The study aimed to “determine the conditions of rural education in Jalisco, Coquimbo and Victoria, recognizing the contextual differences and highlighting the educational policies of educational leadership, defining the dynamics of rural education in each country” and used comparative observables such as a) the historical references of the educational systems, b) the geographic conditions of the states, c) the composition of each educational system, d) the effects of neoliberal policies on rural education and d) the training and access to the management function at the basic, public level.